Evaluation of Chopped Switchgrass as a Litter Material - Davis, J.D.; Purswell, J.L.; Columbus, E.P.; Kiess, A.S. (International Journal of Poultry Science, 2009)
An alternative broiler litter to pine shavings may be switchgrass, a high yielding forage crop (8-12 tons per acre) that can grow across the Southeastern U.S. A study was conducted to determine the efficacy of chopped switchgrass as a litter material for broiler chickens. Pine Shavings (PS) and Switchgrass (SG) were used as litter treatments with 10 replications each. Body weight, body weight gain, feed consumption, feed conversion, carcass weights and mortality were not different between treatments. However, the incidence of foot pad dermatitis was significantly decreased with SG litter. Live performance and carcass weights were not affected by using chopped SG as a litter material when rearing broilers over a short duration (one flock cycle).